PERTUMBUHAN ENAM KULTIVAR SANSEVIERA TRIFASCIATA DENGAN STEK PANGKAL DAUN - Settings Whika Febria Dewatisari (LPPM Universitas Terbuka, 2015)
The aims of this experiment determined the growth and development of the six cultivars of S. trifasciata by leaf cutting and looked the best growth and development.This study used randomized design experimental with three replications used homogeneous experimental units or no other factors affected the response of outside factors studied.Observations were made every 30 days by measuring buds height, number of buds, root length, and number of roots.The results showed the best average of buds height, root length and root number were on S. trifasciata